High performance semitransparent organic solar cells with 5% PCE using non-patterned MoO3/Ag/MoO3 anode - Upama, M.; Wright, M.; Elumalai, Naveen Kumar; Mahmud, M.; Wang, D.; Chan, K.; Xu, C.; Haque, F.; Uddin, A. (Elsevier, 2017)
Semitransparent organic solar cells are a promising approach to smart window applications and building integration. Here, we demonstrate a high performance semitransparent organic solar cell that incorporates the low bandgap polymer, PTB7, in the photoactive layer and a simple, non-patterned Dielectric/Metal/Dielectric or D/M/D anode (MoO3/Ag/MoO3). The combination of excellent photovoltaic properties of PTB7:PC71BM based solar cell and transparency of the MoO3/Ag/MoO3 anode resulted in an impressive power conversion efficiency of 5% at 18.3% visible light transmission. By tuning the active layer and outer MoO3 layer thicknesses, devices with ∼25% average visible transmission were fabricated, which is considered as a benchmark transmittance for window applications. Transfer matrix modelling (TMM) was used to optimise the active layer and electrode thickness in terms of the optical field in the active layer. Additionally, the color rendering ability was found to be dependent on the active layer thickness, as well as the electrode. Device properties were studied from the perspectives of color rendering property, photovoltaic performance and theoretical optical field distribution.